Beginning Spring - Çalişkan, Mert; Höller, Jũrgen (Wrox, a Wiley brand, 2015)
Beginning Spring is the complete beginner's guide to Java's most popular framework. Written with an eye toward real-world enterprises, the book covers all aspects of application development within the Spring Framework. Extensive samples within each chapter allow developers to get up to speed quickly by providing concrete references for experimentation, building a skillset that drives successful application development by exploiting the full capabilities of Java's latest advances.